Current Concepts in the Diagnosis and Management of Traumatic, Anterior Glenohumeral Subluxations. Issue 3 (20th March 2017) - Gil, Joseph A.; DeFroda, Steven; Owens, Brett D.
Traumatic anterior glenohumeral subluxations comprise the majority of glenohumeral instability events and are endemic in young athletes. Unlike the definitive complete dislocation event, subluxation events may often be more subtle in presentation and, therefore, may be overlooked by clinicians. Glenohumeral subluxation events are associated with a high rate of labral tears as well as humeral head defects. While less is known of the natural history of these injuries, young athletes are at risk for recurrent instability events if not properly diagnosed and treated. While reports of surgical treatment outcomes isolated to subluxation events are limited, arthroscopic and open Bankart repair have been shown to result in excellent outcomes. The purpose of this paper is to review the etiology and pathoanatomy of traumatic anterior glenohumeral subluxations as well as to review the appropriate evaluation and management of patients with this injury.